Perlindungan Data Pribadi Penghadap pada Penyimpanan Minuta Akta Notaris secara Cloud Storage - Baldi, Rivanka Gradian; Salam, Abdul (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The digital transformation of notarial practice has resulted in a fundamental shift from the traditional physical storage of deed minutes to the adoption of cloud-based storage systems. While this transition introduces efficiency and improves archival management, it simultaneously generates new challenges regarding the protection of personal data of parties appearing before the notary, as deed minutes contain highly sensitive information protected under notarial confidentiality. Law Number 27 of 2022 on Personal Data Protection (PDP Law) mandates that notaries acting as data controllers ensure the security, integrity, and confidentiality of personal data, including when stored electronically. Failure to fulfill these obligations may lead to legal consequences in the form of administrative and criminal sanctions. This study adopts a normative juridical approach to examine the protection of personal data in the context of storing deed minutes using cloud storage. The findings reveal that data protection can only be achieved if digital transformation is supported by strong electronic security standards, digital literacy among notaries, ethical awareness, and technical professional guidelines. Ultimately, modernization should reinforce—not diminish—public trust in notarial services.